FAKTOR-FAKTOR PENYEBAB TERJADINYA PENCEMARAN AIR DI SUNGAI BINDU - I Wayan Eka Artajaya, Ni Kadek Felyanita Purnama Putri (Faculty of Law, Mahasaraswati University, Denpasar, 2021)
Indonesia is a very large and wide country, consisting of many islands and abundant natural resources. Natural resources in Indonesia are everything that comes from nature that is used to meet the needs of human life. Generally, natural resources in Indonesia can be classified based on their nature, namely renewable natural resources and non-renewable natural resources. Humans are very dependent on natural resources and the sustainability of natural resources is strongly influenced by human activities. Watershed is one of the natural resources that is very complex and consists of various components that make it up. The functions and benefits of water resources themselves, including rivers, require various efforts to improve and protect water so that it is efficient and effective for living things and the surrounding environment. One of them is the Bindu river in the Kesiman Traditional Village. The Bindu River is widely used by the community, causing water pollution in the Bindu river, such as the Kesiman Traditional Village which has an important role in suppressing the occurrence of water pollution that occurs in the Bindu river. Negara Indonesia merupakan negara yang sangat besar dan luas, terdiri dari banyak pulau dan sumber daya alam yang melimpah. Sumber daya alam di Indonesia merupakan segala sesuatu yang berasal dari alam yang digunakan untuk memenuhi kebutuhan hidup manusia. Umumnya sumber daya alam di Indonesia dapat digolongkan berdasarkan sifatnya yaitu sumber daya alam yang dapat diperbaharui dan sumber daya alam yang tidak dapat diperbaharui. Manusia sangat bergantung pada sumber daya alam dan kelestarian sumber daya alam sangat dipengaruhi oleh aktivitas manusia. Daerah aliran sungai merupakan salah satu sumber daya alam yang sangat kompleks dan terdiri dari berbagai komponen yang menyusunnya. Fungsi dan manfaat sumber daya air sendiri termasuk sungai memerlukan berbagai upaya untuk peningkatan dan perlindungan air agar berdaya guna dan berhasil guna bagi makhluk hidup dan lingkungan sekitar. Salah satunya adalah sungai Bindu yang berada di Desa Adat Kesiman. Sungai Bindu banyak dimanfaatkan oleh masyarakat sehingga menyebabkan terjadinya pencemaran air di sungai Bindu, seperti Desa Adat Kesiman memiliki peranan penting dalam menekan terjadinya pencemaran air yang terjadi di sungai Bindu.